2022
DOI: 10.1038/s41598-022-17924-3
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nano-swirlings for Azo Dye AR183 photocatalytic degradation and antimycotic activity

Abstract: The sol-gel technique was used to fabricate ZnO Nano-swirlings (ZNsw) at a predetermined agitation rate (of >> 1900 rpm), with around 21.94 gm of zinc acetate dihydrate and 0.2 g cetyltrimethylammoniumbromide (CTAB) and a cationic surfactant (drop-wise). The impact of the predetermined agitation condition on the molecular size and morphology of ZNsw is examined, and the outcomes are dissected by useful characterization tools and techniques viz. XRD, SEM embedded with EDS, TEM, FT-IR and UV–visible. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The peaks in all XRD patterns, specifically [1 0 0], [0 0 2], [1 0 1], [1 0 2], [1 1 0], [1 0 3], [1 1 2] and [2 0 1] show diffraction peaks for ZnO nanostructures. This led to the identification of ZnO as an epitaxial phase with a hexagonal lattice ( Umar et al, 2022 ). According to our previous study, the highest peak of 2θ occurred at 36.3°, which was reported all along the orientation [1 0 1] ( Khan et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peaks in all XRD patterns, specifically [1 0 0], [0 0 2], [1 0 1], [1 0 2], [1 1 0], [1 0 3], [1 1 2] and [2 0 1] show diffraction peaks for ZnO nanostructures. This led to the identification of ZnO as an epitaxial phase with a hexagonal lattice ( Umar et al, 2022 ). According to our previous study, the highest peak of 2θ occurred at 36.3°, which was reported all along the orientation [1 0 1] ( Khan et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the optical/structural properties, UV-Visible absorption spectroscopy was used ( Figure 3 ). Both samples displayed significantly narrow absorption bands in the UV-A region between 364 and 382 nm devoid of any other peaks ( Umar et al, 2022 ), signifying combined light wave and electron vibrations of nanoparticles ( Miri et al, 2019 ). However, from ZRT-1 to ZRT-2, the absorption bands’ intensity enhanced slightly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sansenya et al [141] prepared ZnO by a hydrothermal method for the complete photodegradation of RR141 and CR dye. ZnO nanoswirlings fabricated by Umar et al [142] observed 79% AR183 dye degradation under UV light within 80 min.…”
Section: Transition Metal Oxide Catalystsmentioning
confidence: 99%
“…Refs. [ 21 , 35 , 41 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] are cited in Supplementary Materials .…”
mentioning
confidence: 99%